Genetic Variability Analysis and Trait Interrelationship in Helianthus annuus l. across Two Growing Years - Razzaq, Humera; Amjad, Noreen; Bukhary, Zeeshan Ishfaq; Hassan, Waqar ul; Khalid, Muhammad Nouman (Journal of Agriculture and Veterinary Science, 2025)
Edible oil consumption is increasing day by day while its production is stagnant. In Pakistan, there is huge gap between consumption and production. Cottonseed is contributing majorly to local production followed by Brassica and sunflower. Although sunflower is non-conventional crop, but it has great potential to fulfill then gap between consumption and production of edible oil. Sunflower is cross-pollinated crop and has highest genetic variation. There is dire need to explore the genetic potential of cultivated sunflower accessions. Assessment for genetic variability is the main component for effective selection. Achene yield is a complex trait influenced by genetic and environmental factors. Understanding the interrelationship among yield and its contributing attributes is the foundation for effective breeding strategies. This scientific inquiry focuses on accessing genetic variability and interrelationship among key traits across two years 2022 & 2023. Experiment was conducted at the research area of the Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad. The study involved 80 sunflower accessions from diverse sources i.e. national and international organizations grown by using Randomized Complete Block Design with three replications. Data were recorded on achene yield and its related traits for further analysis. Recorded data were subjected to analysis of variance, mean comparison test, and correlation coefficient analysis. The results revealed significant differences among accessions for all the studied traits, suggesting effective selection from germplasm. Among 80 sunflower accessions, Line 48, 49 and 50 had maximum means values for most of the traits. Traits number of leaves, leaf area, and head diameter are selected as selection criteria for improving the oil and achene yield in sunflowers. The study's results provide a solid foundation for breeding programs aimed at improving sunflower yield and productivity across diverse growing seasons.
Keywords: Sunflower; Oilseeds; Genetic Variability; Achene and Oil Yield; Correlation Coefficient